ENHANCING LANGUAGE TEACHING AND LEARNING THROUGH YOUTUBE PLATFORMS: STUDENTS’ AND TEACHERS’ PERCEPTION - Hendar Hendar; Aan Amalia (University of Kuningan, 2024)
This qualitative descriptive study explores the perceptions of lecturers and students towards utilizing the YouTube platform for enhancing language learning and teaching. Amidst the digital revolution, YouTube has emerged as a significant educational tool, offering vast resources for learners and educators in the fields of English and Japanese languages. The study involved 52 students and 11 lecturers from the Faculty of Humanities at Widyatama University, employing questionnaires with both close-ended and open-ended questions to gather data. The results revealed a positive perception towards YouTube, with 89% of lecturers and 88.5% of students recognizing its benefits for language education. Lecturers and students noted YouTube's effectiveness in providing diverse and engaging content, aiding in the development of language skills, and offering accessible materials for better understanding of complex topics. This research underscores YouTube's potential as a valuable educational platform, suggesting its integration into language teaching and learning strategies to optimize educational outcomes. The findings highlight the need for educators to explore digital platforms like YouTube to enhance the learning experience, catering to the evolving needs of 21st-century learners.Keywords: perception, YouTube platform, qualitative research, language learning and teaching, digital education